Formulación de un plan de mantenimiento preventivo, para el área de Exportación 1 de la Empresa Paraíso Del Ecuador, ubicado en el Cantón Mejía- Ecuador - Collaguazo Pulupa, Danny Alexander (2024)
The document arises from the lack of good maintenance management in the sealing machine, which focuses on the production of T-shirt type plastic covers. Products Paraíso del Ecuador, is a reference in vertical manufacturing in mattress production under international quality standards, has a GreenBag line, which helps to preserve the environment, innovated in strengthening flexible plastic product lines, so it is essential to have a proper functioning of its machinery, to ensure that all its plastic products, are with the best quality. The main objective is the formulation of a preventive maintenance plan for the export area # 1 of the company Paraíso del Ecuador, located in Mejía- Ecuador, where the need has arisen to establish an analysis of the types of maintenance, study the most important characteristics to avoid failures. The methodology used for the preventive maintenance plan was developed as follows: the collection of physical and digital data, equipment inventory, inventory of spare parts, criticality analysis, and study of the diverse types of existing maintenance. As a result, a preventive maintenance plan is obtained in export # 1, for the critical equipment. The result is the preventive maintenance plan in the export area # 1, for the critical equipment, and the analysis of spare parts management to guarantee the useful life of the equipment, avoiding unexpected stops and losses in the production generated by corrective maintenance.